Sacred and secular : responses to life in a finite world - Crosby, Donald A. (SUNY Press, 2022)
"The sacred and the secular--or religion and secularity--differ from one another in many ways, but they must also frequently interact with and can instruct and benefit one another in today's world. This is especially so when neither is reduced to an uninformed distortion or stereotype by the other. Careful analysis of their relationships is needed. Such analysis is especially important in the contemporary world, where the two are being challenged, reshaped, and reformed by the sheer number of changing religious and secular perspectives--all of this taking place within the ferment of an increasingly global society. This book explores past and present ways of distinguishing the two with which Donald A. Crosby either takes issue with or finds to be congenial. It also proposes ways in which the two are not only meaningfully distinguished from one another, but also where their mutually beneficial relationships can be highlighted. A particular conception of the nature of religious faith is compared and contrasted with some influential types of secular faith"-- Back cover.
Keywords: Religion.; Secularism.; Religion; religion (discipline); RELIGION / Comparative Religion; Secularism